Variations in nutrient composition and glycemic index of standardized traditional cocoyam and corn-based dishes consumed in Nsukka Local Government Area of Enugu State, Nigeria - Davidson, Gloria Ifeoma; EneObong, Henrieta Nkechi; Nnawuihe, Onyinyechi Olivia (Progress in Nutrition, 2019)
Background and objectives: Glycaemic index (GI) is an important parameter of food quality that compares the hypoglycaemic effect of a test meal with pure glucose. Low glycaemic index diets have been recommended for diabetics. The study was to determine the glycaemic index (GI) of standardized cocoyam and corn-based traditional dishes consumed in south-eastern Nigeria. Methods: Focus group discussions were conducted in eight randomly selected communities in Nsukka LGA to document the variations of each dish and their recipes. These were standardized and prepared. Nutrient compositions of the prepared dishes were determined using standard procedures. A serving portion of each dish containing 50g of available carbohydrate was served to ten healthy adult subjects. Glucose was used as the reference food. The postprandial blood glucose response of the test and the reference meals were measured over two hours at 30 minutes interval. Blood glucose curves were plotted, area under each curve and corresponding glycaemic index value for each dish determined. Data were analyzed using Statistical Product for Service Solution (SPSS). Analysis of variance was used to compare the means. Result: Three variations of cocoyam-based dishes were documented: ‘achicha’(dried cocoyam chips, soaked and steamed) with pigeon pea, ‘achicha’ with fresh ‘akidi’(fresh cowpea in pod) and ‘achicha’ with vegetable (fluted pumpkin leaves). The corn-based dish had two variations: ‘ayaraya oka’ (coarsely ground soaked, steamed corn) with pigeon pea and ‘ayaraya oka’ with fresh ‘akidi’. The dishes had appreciable proximate, vitamin and mineral composition though theier vitamin B2, iron and zinc content were low. The GI of ‘achicha’ with vegetable was 69%, followed by ‘achicha’ with fresh ‘akidi’ (49%) and ‘achicha’ with pigeon pea (47%). The GI of the cocoyam-based dishes were, therefore, within the range of 47 and 69% being highest in ‘achicha’ with vegetable and lowest in ‘achicha’ with pigeon pea. The GI of ‘ayaraya oka’ with pigeon pea and ‘ayaraya oka’ with fresh ‘akidi’ were 69 and 57%, respectively. Conclusion: ‘Achicha’ with pigeon pea, ‘achicha’ with fresh ‘akidi’ and ‘ayaraya oka’ with fresh ‘akidi’ had low glycemic index and could be recommended for diabetics.